2021
DOI: 10.3389/fimmu.2021.744300
|View full text |Cite
|
Sign up to set email alerts
|

RASAL3 Is a Putative RasGAP Modulating Inflammatory Response by Neutrophils

Abstract: As first responder cells in host defense, neutrophils must be carefully regulated to prevent collateral tissue injury. However, the intracellular events that titrate the neutrophil’s response to inflammatory stimuli remain poorly understood. As a molecular switch, Ras activity is tightly regulated by Ras GTPase activating proteins (RasGAP) to maintain cellular active-inactive states. Here, we show that RASAL3, a RasGAP, is highly expressed in neutrophils and that its expression is upregulated by exogenous stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…1G, 1H ). Neutrophil extracellular traps (NETs) formation is another dynamic antibacterial response in neutrophils [ 28 ]. In the NETosis induced by PMA in this study, creatine treatment enhanced the formation of NET structures, which could be observed under fluorescence microscope ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1G, 1H ). Neutrophil extracellular traps (NETs) formation is another dynamic antibacterial response in neutrophils [ 28 ]. In the NETosis induced by PMA in this study, creatine treatment enhanced the formation of NET structures, which could be observed under fluorescence microscope ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the samples were stained with 7-AAD and analyzed on the same day without fixation. The NETosis assay was performed by a previously reported method with minor modification [ 28 , 29 ]. Briefly, peripheral blood was treated with 1× red blood cell (RBC) lysis buffer at room temperature (RT) for 10 min, washed and fixed with 1% paraformaldehyde (PFA) at RT for 10 min, and subjected to staining for surface markers as well as nuclear and DNA staining.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We studied a RasGAP, RASAL3, which was recently characterized for its immunomodulatory functions in neutrophils. It is possible that these effects on immune response were due to inhibition of migration, but this was not assessed 95 . For our experiment, we transiently recruited RASAL3 to the leading front by shining light periodically near the existing protrusions, as shown by the dashed white box (Figure 3G, Video S8).…”
Section: Resultsmentioning
confidence: 99%
“…Neutrophils are frequently studied due to their central role in the innate immune system, specifically their involvement in antibacterial immunity (5). Under bacterial invasion, neutrophils function to eliminate the bacteria through several activities, such as phagocytosis, neutrophil extracellular trap (NET) formation, and reactive oxygen species (ROS) production (5)(6)(7). Thus, it is expected that the impairment of neutrophil functioning will result in the collapse of the primary defense against pathogen colonization.…”
Section: Introductionmentioning
confidence: 99%